Respostas

2013-05-25T17:24:46-03:00

A) 

1) Calculando o Δ da equação completa:

Δ = b2 - 4.a.c 
Δ = -162 - 4 . 1 . 0 
Δ = 256 - 4. 1 . 0 
Δ = 256

 

Aplicando Bhaskara:

x = (-b +- √Δ)/2a

 

x' = (--16 + √256)/2.1     x'' = (--16 - √256)/2.1 x' = 32 / 2     x'' = 0 / 2 x' = 16     x'' = 0

 

 B)

Δ = b2 - 4.a.c 
Δ = 02 - 4 . 1 . -16 
Δ = 0 - 4. 1 . -16 
Δ = 64

 

x = (-b +- √Δ)/2a

 

x' = (-0 + √64)/2.1     x'' = (-0 - √64)/2.1 x' = 8 / 2     x'' = -8 / 2 x' = 4     x'' = -4 C)Δ = b2 - 4.a.c 
Δ = 32 - 4 . 1 . -4 
Δ = 9 - 4. 1 . -4 
Δ = 25
x = (-b +- √Δ)/2a

 

x' = (-3 + √25)/2.1     x'' = (-3 - √25)/2.1 x' = 2 / 2     x'' = -8 / 2 x' = 1     x'' = -4

   

2013-05-25T17:26:56-03:00

Envio-lhe uma solução possível. Atenciosamente.